2013
DOI: 10.1177/1753193413517621
|View full text |Cite
|
Sign up to set email alerts
|

Pathoanatomy and treatment modifications of metacarpophalangeal joint locking of the thumb

Abstract: Ten patients with metacarpophalangeal joint locking of the thumb were studied. Three of them underwent surgical release. During surgery, it was found that the radial sesamoid was seated in a cartilage defect on the volar aspect of the metacarpal head. It appeared that the defect was created by the proximal edge of sesamoid. When the abductor pollicis brevis and flexor pollicis brevis muscles were partially detached from their insertion at the base of the proximal phalanx, the locking could be successfully rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…The pathology of locking is controversial. Previous studies suggested that the pathology of locking is based on the entrapment of the sesamoid bone, 3,4 proximal end of the volar plate, 5 and deformity of the distal metacarpal head. 2 Ueda et al reported a case of locking of the MP joint of the thumb due to an intra-articular loose body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathology of locking is controversial. Previous studies suggested that the pathology of locking is based on the entrapment of the sesamoid bone, 3,4 proximal end of the volar plate, 5 and deformity of the distal metacarpal head. 2 Ueda et al reported a case of locking of the MP joint of the thumb due to an intra-articular loose body.…”
Section: Discussionmentioning
confidence: 99%
“…7 The tension of the abductor pollicis brevis and flexor pollicis brevis might also contribute to locking since the release of these muscles led to successful reduction of locking. 4 Based on the CT and intraoperative findings, the pathology of locking of the MP joint of the was influenced by several factors such as the sesamoid bone, volar plate, and accessory ligament, so-called "constricting bundle." 8 Yamanaka et al reported that the pathology of locking of the thumb is induced by the following mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Locking of the thumb metacarpophalangeal (MP) joint refers to a condition that causes a fixed state of the MP joint with a slight hyperextension deformity and motion restriction [1][2][3][4][5]. It can result from relatively minor hyperextension injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some controversies, an incarcerated volar plate, accessory collateral ligament, or entrapped radial sesamoid are considered to be possible causes of locking [1,3]. Closed reduction can be attempted initially, but open reduction is often required, particularly when the presentation or diagnosis is delayed [4]. In the absence of clinical information, radial sesamoid movement or entrapment at the 1st MP joint is often overlooked on routine anteroposterior and lateral radiographs because of the bony overlap and variable degree of normal range of motion of the 1st MP joint [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation